Designer drug poisonings as a growing clinical problem - Barbara Zofia Klatka; Anna Katarzyna Orzeł; Dominika Janeczko; Magdalena Hołowczuk; Michał Jerzy Terpiłowski; Michał Tchórz (Kazimierz Wielki University, 2019)
Introduction and purpose: Designer drugs also known as legal highs, research chemicals or herbal highs become more and more popular not only in Poland but also in other countries around the world. That might have many reasons but the most crucial is their easy availability and rather cheap price in comparison to other psychoactive substances. Material and methods: We analyzed the data of patients hospitalized in years 2013-2018 in the Toxicology Department in Lublin and evaluated patients hospitalized due to psychoactive substance poisoningT40 according to ICD10). Moreover the review of available scientific articles was done. Results: After analysis the data of patients hospitalized in years 2013-2018 we can observe increasing tendency of poisonings. The growing number of designer drug poisonings may be the result of many factors - the phenomenon of these substances is based not only on a wide range of products, but also on various advertising strategies and patterns of use. Conclusions: There can occur big diagnostic difficulties due to unpredictability of the course of poisoning and unpredictability of composition. Therefore it is very important to react quickly and choose the right treatment. Many of these poisonings are really severe and often cause death. It is worth saying that side effects occur more often in combined preparations. It is also very important to educate young people and warn against using NPS, which are particularly dangerous and risky for human organism.